(untitled) (Nueva Epoca, 2020)
The actions of responsibility of the administrators are regulated in the General Law of Companies — 19550 t.o.— (arts. 276 to 278 LGS ) and in the Bankruptcy Law — 24522 t.o.— (arts. 173 to 176 LCQ ). Now: «responsibility» understood as an obligation to repair the damage caused to another (art. 1716 of the Civil and Commercial Code of the Nation (hereinafter CC y C ) has a wide and complex field of application and it is necessary to make the rules compatible of the special laws, in our case law 19550 and law 24522, with the regime established by the new Code. With this perspective and based on these premises, we will approach the analysis of liability actions against representatives and administrators of companies provided for in both company legislation and bankruptcy legislation, without entering into the analysis the liability actions against other non-representative third parties (art. 173, second paragraph LCQ ).